Custos no setor público: uma proposta de implantação do sistema de custos da Universidade Federal Rural do Semi-Árido - Freitas Filho, Roberto Carvalho de Oliveira (Universidade Federal Rural do Semi-Árido, 2021)
Public organizations management is constantly changing to enable process control and increase efficiency. Therefore, Federal Universities need to constantly develop their management tools to achieve their goals, aiming performance budgeting, social responsibility, and transparency with public resources. In this sense, UFERSA (Semi-Arid Federal University) instituted a cost commission, which instituted a Cost Accounting Manual (CAM), which contains the institution's cost system, however, it is not yet being implemented. Regarding this matter, the present work has as its general objective the elaboration of the action plan to implement the cost calculation system foreseen in the UFERSA Cost Calculation Manual. This research methodology was classified as an applied qualitative descriptive research, towards its procedures, those were interviews, bibliographical and documental research, and study case. The results of the study allowed the description of the UFERSA Cost Accounting Manual; the mapping of each process involving costs according to Diminutive Equity Variations, containing the current flow, through a generic cost center and the flow in accordance with the present proposal, indicating a definitive cost center for treatment; it was presented how the cost information should be treated to be allocated to UFERSA's undergraduate and graduate courses; and finally, an Action Plan was proposed for the implementation of the Cost Accounting System, with Management being able to choose to create a Division for its purpose or annually appoint a Commission to be responsible for this expenditure account system. Another action was the elaboration of a multiple-choice questionnaire so that managers can, at the time they are making their request, use a cost center code, to allocate the cost in a detailed manner
Keywords: Eficiência; Sistema de custos; Plano de ação; Efficiency; Cost system; Action plan; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA